Direct electron attachment to fast hydrogen in 10−9 contrast 1018 W cm−2 intense laser solid target interaction. (11th November 2020) - Tata, Sheroy; Mondal, Angana; Sarkar, Soubhik; Lad, Amit D; Colgan, James; Pasley, John; Krishnamurthy, M
Abstract: The interaction of an ultra-short (<30 fs), high-contrast (<10 −9 ), high-intensity (>10 18  W cm −2 ) laser pulse with a solid target is not generally known to produce and accelerate negative ions. The transient accelerating electrostatic-fields are so strong that they ionize any atom or negative ion at the target surface. In spite of what may appear to be unfavourable conditions, here it is reported that H − ions extending up to 80 keV are measured from such an interaction. The H − ion flux is about 0.1% that of the H + ions at 20 keV. These measurements employ a recently developed temporally-gated Thomson parabola ion spectrometry diagnostic which significantly improves signal-to-noise ratios. Electrons that co-propagate with the fast protons cause a two-step charge-reduction reaction. The gas phase three-body attachment of electrons to fast neutral hydrogen atoms accounts for the measured H − yield. It is intriguing that such a fundamental gas-phase reaction, involving the attachment of an electron to a hydrogen atom, has not been observed in laboratory experiments previously. Laser-produced plasma offers an alternative environment to the conventional charged particle beam experiments, in which such atomic physics processes can be investigated.